The Influence Of Contemporary Art Gallery Development As A Tourist Attraction On Tourist Visit Intention - Khairunnisa Khairunnisa; Yulita Suryantari (UNIVED Press, 2025)
This study analyzes the influence of developing contemporary art galleries as tourist attractions on tourist visit intention. Using a quantitative descriptive approach and causal method, questionnaires were given to 100 respondents who had visited contemporary art galleries at TMII. Data were analyzed with SmartPLS 3.2.9. The results show that reliability and responsiveness have a significant influence on return visit intention. reliability has a strong relationship with visit intention, while responsiveness has a very significant influence. In contrast, perceived beliefs and tangibles showed no significant effect. These findings emphasize the importance of reliability and responsiveness in influencing tourists' decision to revisit contemporary art galleries. By improving service reliability and responsiveness, art galleries can increase visitor satisfaction and loyalty, and encourage tourist revisits.